The artistic composition of Arabic calligraphy in the Kiswah of the Holy Kaaba: a descriptive and analytical study - Alashari, Duaa; Berghout, Abdelaziz (ISTAC-IIUM Publication, 2024)
The Kaaba's Kiswah carries inherited aesthetics with an ancient historical and cultural character. The Kiswah of the Kaaba is one of the earth's holiest and most precious fabrics, as it covers the Sacred House of Allah and carries sublime sanctity meanings. Therefore, this study aims to provide an accurate and detailed descriptive study of the totality of Arabic calligraphy and calligraphic formations in form and textual content during the reign of King Salman Al Saud. The study also aims to provide a complete analytical description of the written contents of the lines and calligraphic formations, the type of compositions, and the general structure of the compositions on all four sides of the Holy Kaaba. The approach followed in the study is the content analysis approach. The current study will be based on observation. The study found that the covering of the Holy Kaaba is based in its design on a group of Qur'anic verses selected by scholars.